Sociology of terrorism: A key to understanding social origins? [Terörün sosyolojisi: Toplumsal kökenlerianlama ÿmkâný] - (:unkn) unknown (International Relations Council of Turkey, 2010)
Organized violence and terrorist attacks with global connections and transnational implications not only contribute to the deterioration of regional and international relations but also tend to locate and confi ne international relations analysis to the axis of securitization. Much of the studies on collective violence and terrorism focus on security aspects of such acts but fail to address social roots of confl icts adequately. Th is article seeks to draw attention to the signifi cance of sociological analysis of acts of terrorism in light of recent scholarship. It argues that without a thorough analysis of social contexts of such acts, fi ghting terrorism and violence will not be eff ective and international relations will deteriorate further. Therefore the article concludes that a 'sociology of terrorism' based on.
Keywords: New Colonialism; Religion; Sociology; Terrorism; Violence